Utilizing Case Studies to Increase Engagement and Better Learning Outcomes in Secondary Science Education (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
A significant portion of secondary school students lack engagement in science classrooms, and a possible solution could be to listen to how they prefer to learn. A popular answer students suggest for learning information is through real world applications. The use of case studies is a promising answer that implements real world applications in science education and accompanies important scientific explanations to life outside of the classroom. Case-based learning can positively affect important factors of engagement and is an effective approach when compared to traditional teaching methods. Due to an increase in engagement, students may also benefit from case studies by improving their learning outcomes. With the evidence provided, case studies are worthwhile to implement in secondary science classrooms.
Keywords: case studies; case-based learning; engagement; learning outcomes; secondary science education; motivation; assessment